(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
“What harm can there be in following the rhythm of things with your feet, in becoming familiar with the leaks, in refining your pulse,” reads one of the poems in this first book by Juan Cristóbal Romero. (Reseña)